Donors in transition and the future of development cooperation: What do the data from Brazil, India, China, and South Africa reveal?. (15th September 2019) - Gulrajani, Nilima; Faure, Raphaëlle
Summary: How are Development Assistance Committee (DAC) donors evolving their financial flows and aid modalities in response to the growing influence and economic power of Southern BRICS? After presenting the shifting landscape of international development cooperation, we explore five hypotheses about the changing nature of DAC aid allocation patterns and modalities in BRICS countries. In our conclusion, we reflect on the evolution of DAC engagement in Brazil, China, India, and South Africa (BASIC countries) and what it might mean for all official donors. Our assessment is that the changing geopolitical environment for development cooperation is once again privileging economic diplomacy concerns within DAC donors, propelling specific kinds of decisions about the choice of instruments, sectors, and modalities in BASIC countries. It would appear that the administrative practice of foreign aid is increasingly derived from changes within the institutional environment for international development.